Study of the elastic scattering of 15N ions on 9Be nuclei at Elab=18,75 MeV - Burtebayev, N.; Morzabayev, A.K.; Amangeldi, N.; Mauyey, B.; Yergaliuly, G.; Alimov, D.K. (Recent Contributions to Physics, 2019)
In present work, we measured the angular distributions of elastic scattering of 15N ions on 9Be nuclei at an energy of Elab = 18.75 MeV in the range of angles θ cm from 43 ° to 164 °. The extraction of 15N ion beams was carried out at the Nur-Sultan branch of the INP RK on the DC-60 cyclotron. The particles were detected in the framework of the ∆Е-Е technique using the silicon surface-barrier detectors dE and E from ORTEC, the thickness of which was 8 and 300 microns, respectively. 9Be films with a thickness of about 31 μg / cm2 were used as targets. The purpose of this work was to obtain new data on the parameters of the optical potential for the 15N + 9Be system.The obtained data were analyzed using the Fresco and DFPOT codes, within the framework of the optical model (OM) and the duble folding method as a result of which several sets of optical parameters were obtained.